Efficacy of sodium new houttuyfonate against Aspergillus flavus: insights from in vitro and in vivo models of invasive pulmonary aspergillosis - Bao, Yilin; Feng, Dingxian; Zhang, Jinping; Hu, Xiaoyan; Yang, Xinyou; Mao, Yingyu; Song, Zhangyong (Frontiers in Pharmacology, 2025)
Aspergillus flavus is an opportunistic pathogenic fungus that causes invasive aspergillosis in humans. Due to the limited variety and quantity of clinical antifungal drugs and their adverse effects, the development of new broad-spectrum antifungal drugs is urgently required. Our preliminary research showed that sodium new houttuyfonate (SNH) was efficacious against A. fumigatus infection, but its effects against A. flavus remain unknown. In this study, we used the microdilution broth susceptibility method to determine the antifungal activities of four antifungal drugs and SNH against 12 clinical A. flavus strains, in vitro. To confirm the therapeutic effect of SNH on A. flavus infection, we established a mouse model of invasive pulmonary aspergillosis (IPA) with the nasal drip method. All the strains tested were resistant to fluconazole but sensitive to itraconazole, voriconazole, and amphotericin B. The minimum inhibitory concentration to inhibit the growth of 90% of cells (MIC90) of SNH against the test strains was 64–128 μg/mL. After the IPA mouse model was treated with SNH, the expression of genes encoding interleukin 6 (IL-6), IL-1β, and tumor necrosis factor α was significantly reduced. SNH also reduced the fungal load in the mouse lung, the extent of pathological damage, and the neutrophil/lymphocyte ratio in the blood. These findings indicated the potential utility of SNH in the treatment of A. flavus infections.